Regulation of financial systems and economic growth in OECD countries An empirical analysis - de Serres, Alain (OECD Publishing, 2007)
The operation of the financial system can have a key impact on economic growth and the stability of the economy. It affects long-term economic growth through its effect on the efficiency of intermediation between the savers and final borrowers of funds; through the extent to which it allows for monitoring of the users of external funds, affecting thereby the productivity of capital employed; and through its implications for the volume of saving, which influences the future income-generating capacity of the economy. It affects the stability of the economy because of the high degree of leverage of its activities and its pivotal role in the settlement of all transactions in the economy, so that any failure in one segment risks undermining the stability of the whole system